Comparison of aerobic capacity on different levels of table tennis players: using two competitive table tennis-specific aerobic test - Song, T. F.; Liew, E.; Wu, S. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Aerobic endurance is important for table tennis (TT) players. At an elite level, it is also paramount to facilitate recovery between matches. While the majority of prior research has already developed a sport-specific aerobic capacity test for TT, it did not cover enough intensity variation for reliable testing. The purpose of the current study was to estimate the differences in aerobic performance between the two groups of TT players in two kinds of TT-specific aerobic test. METHODS: Twenty-two male elite TT players were recruited, eleven of whom were adult athletes aged between U18 and U22, and the other eleven were youth athletes (U14-17). Two TT-Specific Aerobic Tests were used to assess players` aerobic capacity, which comprised the Incremental TT-Specific Aerobic Test (ITTSAT) and the Multistage TT-Specific Aerobic Test (MTTSAT). In the ITTSAT, TT players performed from session 1 to session 2 (with frequencies of approximately 48 and 57 balls/min, respectively, with 6 minutes per stage) until voluntary exhaustion, with a mechanical ball thrower simulating forehand two-point mobile attacks. Regarding the MTTSAT, it consisted of an initial frequency of 44 balls/min and increments of 4 balls/min every 3 minutes (e.g., 48, 52, 56, 60, and 64 balls/min). Changes in heart rate and total sporting times were measured to determine the TT players` physiological responses and sport performance. RESULTS: The results revealed that the time spent in individual practice showed significant differences among two groups. U14-17 TT players were more time than the U18-22 TT players. There were no significant differences in ITTSAT total sporting times (668.73s vs. 548.45s, p =.05) and heart rate among groups. In contrast, the U14-17 group demonstrated higher total sporting times than the U18-22 group (932.18s vs. 736.10s, p